Liposomes, lipid bilayers and model membranes : from basic research to application - Pabst, Georg; Kučerka, Norbert; Nieh, Mu-Ping; Katsaras, J. (John), 1958- (CRC Press, Taylor & Francis Group, 2014)
"With contributions from leading researchers in their fields, this book provides a comprehensive collection of state-of-the-art lipid/model membrane research and industrial/technological applications all in one volume. It is divided into two sections. The first section covers recent lipid/model membrane research, while the second provides examples of how lipid systems have been successfully used in the pharmaceutical, textile, and food industries."--